Damage by Stator championi (Sharp) (Coleoptera; Bruchidae) in seeds of Bixa orellana - Santos, Germi P.; Zanuncio, Teresinha V.; Zanuncio, Jose C.; Molina-Rugama, Adrian J. (Bosque (Valdivia), 1996)
Fruits of Bixa orellana (Bixaceae) were collected in Viçosa, Minas Gerais State, Brazil, and were brought to the Forest Entomology Laboratory of the Federal University of Viçosa 2.54% of all the seeds were damaged by Stator championi (Sharp) (Coleoptera; Bruchidae). This species has been found from Brazil to Costa Rica and is aparently limited to B. orellana seeds. Viability of S. championi, from eggs to adult, was 79.5% with comsumption of 1.83 mg per B. orellana seed for each insect.